2020
DOI: 10.1093/molbev/msaa317
|View full text |Cite
|
Sign up to set email alerts
|

Run or Die in the Evolution of New MicroRNAs—Testing the Red Queen Hypothesis on De Novo New Genes

Abstract: The Red Queen hypothesis depicts evolution as the continual struggle to adapt. According to this hypothesis, new genes, especially those originating from nongenic sequences (i.e., de novo genes), are eliminated unless they evolve continually in adaptation to a changing environment. Here, we analyze two Drosophila de novo miRNAs that are expressed in a testis-specific manner with very high rates of evolution in their DNA sequence. We knocked out these miRNAs in two sibling species and investigated their contrib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 57 publications
1
16
0
2
Order By: Relevance
“…We and others previously reported that miR-983 has evolved adaptively in both D. melanogaster and D. simulans ( Lyu et al 2014 ; Mohammed et al 2014 ). Consistent with the expectation of distinct seed sequences, which are crucial for target recognition ( Agarwal et al 2018 ), loss-of-function mutants of miR-983 exhibit divergent mis-expression of genes between D. melanogaster and D. simulans ( Zhao et al 2021 ). However, it is unclear whether such divergence is caused by changes in miR-983 or in genomic contexts.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…We and others previously reported that miR-983 has evolved adaptively in both D. melanogaster and D. simulans ( Lyu et al 2014 ; Mohammed et al 2014 ). Consistent with the expectation of distinct seed sequences, which are crucial for target recognition ( Agarwal et al 2018 ), loss-of-function mutants of miR-983 exhibit divergent mis-expression of genes between D. melanogaster and D. simulans ( Zhao et al 2021 ). However, it is unclear whether such divergence is caused by changes in miR-983 or in genomic contexts.…”
Section: Resultsmentioning
confidence: 55%
“…To overcome the caveats of previous approaches, we used gene replacement and single-cyst RNA-seq analysis. The trans -regulatory element we analyzed is an adaptively evolving microRNA (miRNA), miR-983, which shows sequence divergence between Drosophila species ( Lyu et al 2014 ; Mohammed et al 2014 ), possesses a large number of targets, exhibits testis-preferential expression ( Lyu et al 2014 ; Mohammed et al 2014 ; Mohammed et al 2018 ), and affects different components of male fitness ( Lu et al 2018 ; Zhao et al 2021 ) so is suitable for this study. Our results suggest that despite antagonism with the often-predominant cis effects, trans regulators may reduce pleiotropy and respond to natural selection via spatiotemporally specific regulation.…”
Section: Introductionmentioning
confidence: 99%
“…New genes continuously contribute to genetic novelty and offer a unique opportunity to understand the phenotypic divergence between species and the evolution of genetic regulatory networks (Tang et al, 2010;Chen et al, 2012;Ross et al, 2013;Zhao et al, 2021). As key players in gene regulation, miRNAs repress their targets weakly but broadly in animals (Zhao et al, 2017;Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The long-term survival of these novel miRNAs remains unclear. Previously we have shown that miR-975 exerts different influences on male fertility between D. melanogaster and D. simulans, and its lossof-function might be adaptive in some lineages (Lu et al, 2018a(Lu et al, , 2018bZhao et al, 2021). Another good example in Drosophila is the mir-310/311/312/313 cluster (mir-310C), which is another adaptive miRNA cluster with a same age as mir-972C (Lu et al, 2008;Lyu et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation